Manajemen Kepala Madrasah dan Guru Pembina dalam Optimalisasi Kegiatan Ekstrakurikuler di MTs Baitul Makmur - Arista, Helsi; Harmi, Hendra; Baryanto, Baryanto (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2024)
This research aims to determine the management of Madrasah Heads and Supervising Teachers in Optimizing Extracurricular Activities at MTs Baitul Makmur. has quite complex problems, one of the causes is that the movement of extracurricular activities is not optimal enough due to a lack of coordination between the Head of the Madrasah, the guidance teacher, and the students of Madrasah Tsanawiyah Baitul Makmur. This research describes the management of Madrasah Heads and Supervising Teachers in Optimizing Extracurricular Activities at MTs Baitul Makmur which includes Planning, Organizing, Actuating, Controlling. This research data was collected through observation, interviews and documentation. Using a qualitative research method with a descriptive approach, as well as a type of sociological research using a field survey method. The informants involved in this research were the Head of Madrasah, Deputy Head of Student Affairs, mandatory extracurricular supervisor and selected extracurricular supervisor at Madrasah Tsanawiyah Baitul Makmur. The research results show that 1. Madrasah Head Management in Optimizing Extracurricular Activities at MTs Baitul Makmur, namely developing existing systems starting from Planning, Organizing, Actuating, Controlling. 2. Management of Supervising Teachers in Optimizing Extracurricular Activities at MTs Baitul Makmur is quite good starting from Planning, Organizing, Actuating, Controlling. 3. Supporting factors and inhibiting factors in Optimizing Extracurricular Activities at MTs Baitul Makmur, supporting factors such as appreciation for winners of extracurricular activity competitions, inhibiting factors are things that hinder such as the regeneration of extracurricular members at MTs Baitul Makmur